Multifunctional polyacrylamide/hydrated salt/MXene phase change hydrogels with high thermal energy storage, photothermal conversion capability and strain sensitivity for personal healthcare. (22nd March 2023) - Qi, Xiaodong; Zhu, Tingyu; Hu, Wenwen; Jiang, Wanjun; Yang, Jinghui; Lin, Qing; Wang, Yong
Abstract: Flexible and light/electrical responsive phase change materials (PCMs) provide significant application prospects in the thermal management and health monitoring of humans. However, the facile fabrication of flexible and multi-stimulus responsive PCMs remains a great challenge. Herein, we proposed a one-step photoinitiated polymerization strategy to prepare flexible phase change hydrogels, which were composed of hydrated salts (sodium sulfate decahydrate, SSD) and polyacrylamide (PAM) hydrogel and MXene nanosheets. The three-dimensional PAM/MXene network efficiently encapsulated the SSD, thus showing high dimension retention ratio of 98.1%, latent heat value of 163.3 J/g and excellent room-temperature flexibility. By triggering the melting-crystallization transition of SSD, the hydrogels showed tunable modulus variations and temperature sensitivity. Benefiting from the electrical MXene nanosheets and SSD crystals, these hydrogel-based sensors displayed good sensitivity (gauge factor of 3.36) with a large strain range (300%) and reliable durability (200 stretching cycles). More importantly, the PAM/SSD/MXene hydrogels exhibited remarkable solar-thermal energy conversion and storage performances due to the incorporation of MXene nanosheets, which could be applied in the photothermal therapy of human body at a constant temperature of ∼35 °C. These flexible phase change hydrogels with moderate phase transition temperatures as well as strain sensing and solar-thermal energy storage functions hold great application potential for wearable thermal management and healthcare devices. Graphical abstract: Image 1